FACTORS THAT ENCOURAGE STUDENTS CHOOSING EDUCATION PROGRAM BUILDING TECHNIQUES FT-UNP - 444-450 , Adriana Pebriari (Universitas Negeri Padang, 2015)
Abstract This study aims to reveal the factors that encourage students choose courses Education Engineering Building FT-UNP in terms of intrinsic and extrinsic factors. This research is descriptive. Total population of 65 students of Technical Education Building (S1) forces in 2014, with a sample of 56 students. Samples were taken with a probability sampling technique type of simple random sampling. Data were collected using a questionnaire with Likert scale using four answer choices. The number of statements in the questionnaire as much as 40 point statement. These results indicate that the factors that encourage students to choose courses consist of two factors, namely intrinsic and extrinsic factors. Intrinsic factors consist of interests, abilities, and goals. The dominant factor is the intrinsic interest of the students themselves. While extrinsic factors consist of family, peers, teachers, and economics. Extrinsic factors that encourage students choose courses Education Engineering Building is the economy. Keywords: Incentives, Students, Education Building Techniques